(3TQM QSGdI aj GdeYGfjs - (3eLghds
(3ChdgG (B:s
(3HSe Gddg (B... (3NU GdEfSGf HeYQaI ChVGY GdcdGe CeQ ejRg Yf ZjQg HgG Ydi Cf GdHGA OGNdI Ydi GdeNUhU Ydi WQjb bhd GHf GdMGLH aj HMK GdefOhH hGNJU HhGh heHGfjg LeY GdeHfj hGdeQGO HgG GdcdeI GdJj (B...s
(3BNQgG (B:s
... (3HJbOjQ Gdbhd Ydi eG hVY aj ZjQ ehVY , bhdg dG Ydi GYJHGQ GdfhGOQ ajg Cf PcQgG GddaR hGQOI daXg faSg efg ZjQ JGQI Hd TGFY aj GdGSJYeGd hdbGFd Gf jbhd Ydi gPG GdJbOjQ jdRe (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GddZIs